Acute Enterocyte Adaptation to Luminal Glucose: A Posttranslational Mechanism for Rapid Apical Recruitment of the Transporter GLUT2 - Chaudhry, Rizwan M. (2011)
BACKGROUND: Glucose absorption postprandially increases markedly to levels far greater than possible by the classic glucose transporter sodium-glucose cotransporter 1 (SGLT1). HYPOTHESIS: Luminal concentrations of glucose >50 mM lead to rapid, phenotypic, non-genomic adaptations by the enterocyte to recruit another transporter, glucose transporter 2 (GLUT2), to the apical membrane to increase glucose absorption. METHODS: Isolated segments of jejunum were perfused in vivo with glucose-containing solutions in anesthetized rats. Carrier-mediated glucose uptake was measured in 10mM and 100 mM glucose solutions (n=6 rats, each) with and without selective inhibitors of SGLT1 and GLUT2. RESULTS: Mean rate of carrier-mediated glucose uptake increased in rats perfused with 100 mM versus 10 mM glucose to 13.9±2.9μmol from 2.1±0.1μmol, respectively (p<0.0001). Using selective inhibitors, the relative contribution of GLUT2 to glucose absorption was 56% in the 100 mM concentration of glucose compared to the 10 mM concentration (27%; p<0.01). Passive absorption accounted for 6% of total glucose absorption at 100 mM glucose. CONCLUSION: A small amount of GLUT2 is active at the lesser luminal concentrations of glucose, but when exposed to concentrations of 100 mM, the enterocyte presumably changes its phenotype be recruiting GLUT2 apically to markedly augment glucose absorption.